Dermatologic Adverse Events Following Afatinib in a Woman with Non-Small-Cell Lung Cancer: A Case Report - Tsaqilah L; Putri AD; Avriyanti E (Clinical, Cosmetic and Investigational Dermatology)
Laila Tsaqilah, Ananda Dwi Putri, Erda Avriyanti Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Laila Tsaqilah, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6282284474849, Email laila.tsaqilah@gmail.comAbstract: Epidermal growth factor receptor inhibitors (EGFRI) are biological factors used in several types of cancer, including non-small-cell lung cancers (NSCLC). One of the EGFR inhibitors that has been approved for NSCLC is afatinib. Dermatologic adverse events are the most commonly reported and may impair the patient’s compliance to the therapy as it causes aesthetic discomfort and significantly impact the patient’s quality of life. We report a case of 31-year-old woman diagnosed with stage IV-NSCLC and treated with afatinib since nine months prior to consult who presented with acneiform rash on the face, trunk, both arms and legs; pruritic pustules and waxy scales on the scalp; xerosis and pruritus of the skin; paronychia on both toes; hair changes on the scalp, eyebrows, eyelashes, and hypertrichosis of the face. Microscopic examination with Gram smear from periungual skin showed polymorphonuclear cells (PMNs) and Gram-positive cocci bacteria. Trichoscopy examination of the hair on the scalp revealed tapering hair, pili torti, follicular hyperkeratosis, multiple hair tufts with erythema, and scaling of the skin; the eyebrow and eyelashes revealed pili torti and tapering hair. The administration of afatinib was continued and the patient was treated with moisturizer, sunscreen, and mild cleanser, topical antibiotic, and topical steroid along with oral doxycycline and oral cetirizine for four weeks. Significant clinical improvement and Dermatology Life Quality Index (DLQI) score was seen on the fourth week of observation. Dermatological adverse events present the greatest concern with EGFRIs use because it can lead to infection, pain, depression, and low self-esteem, moreover, misdiagnosis may lead to treatment discontinuation. Recognizing clinical signs, implementing preventive efforts, and appropriate management are important to improve the quality of life and patient compliance for effective therapy of underlying malignancy.Keywords: afatinib, dermatological adverse effects, EGFR inhibitor, skin toxicity